2014
DOI: 10.5664/jcsm.4042
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Vigilance Task Demonstrates Impaired Vigilance in Disorders with Excessive Daytime Sleepiness

Abstract: Study Objective: The Psychomotor Vigilance Task (PVT) is one of the leading assays of sustained vigilant attention in sleep research and highly sensitive to the effects of sleep loss. Even though PVT is widely used in sleep deprivation studies, little is known about PVT performance in patients suffering from sleep-wake disorders. We aimed to quantify the impact of sleep-wake disorders on PVT outcome measures and examine whether PVT can distinguish between healthy controls and patients with sleep-wake disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 33 publications
3
64
0
Order By: Relevance
“…29 In elderly individuals with OSA, Kim et al observed a significant association between impaired PVT performance and subjective daytime sleepiness (measured by ESS), but not objective daytime sleepiness (measured by MSLT). 19 Similarly, our findings in middle-age OSA patients indicate that impaired PVT performance is significantly associated with subjective but not objective daytime sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…29 In elderly individuals with OSA, Kim et al observed a significant association between impaired PVT performance and subjective daytime sleepiness (measured by ESS), but not objective daytime sleepiness (measured by MSLT). 19 Similarly, our findings in middle-age OSA patients indicate that impaired PVT performance is significantly associated with subjective but not objective daytime sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…PVT is one of the leading assays of sustained attention in the sleep-related research and is highly sensitive to the effect of sleep loss (Deurveilher, Bush, Rusak, Eskes, & Semba, 2015). Studies in rats of chronic sleep restriction or sleep deprivation and in patients with sleep-wake disorders or obstructive sleep apnea showed that poorer PVT performance was associated with more sleep loss and excessive daytime sleepiness (Batool-Anwar et al, 2014;Deurveilher et al, 2015;Dinges et al, 1997;Doran, Van Dongen, & Dinges, 2001;Oonk, Davis, Krueger, Wisor, & Van Dongen, 2015;Thomann, Baumann, Landolt, & Werth, 2014). Insomniacs often complain about insufficient sleep and sleepiness in the daytime that make daytime alertness and sustained attention impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared pupillometry, which measures pupillary oscillations in darkness, has also demonstrated potential utility to quantify drowsiness in mood-disordered patients [31]. Other measures of neurobehavioral alertness, such as the psychomotor vigilance task (PVT), which correlates poorly with the MSLT [51], may also be useful in the diagnosis of CNS hypersomnias and measuring response to treatment [52, 53]. Finally, the use of auditory evoked potentials as an objective measure of sleep inertia has also shown promise as a measure in the assessment of CNS hypersomnias [21].…”
Section: Discussionmentioning
confidence: 99%